Mediterranean Diet and Physical Activity Decrease the Initiation of Cardiovascular Drug Use in High Cardiovascular Risk Individuals: A Cohort Study - Margarita Ribó-Coll; Sara Castro-Barquero; Camille Lassale; Emilio Sacanella; Emilio Ros; Estefanía Toledo; José V. Sorlí; Andrés Díaz-López; José Lapetra; Carlos Muñoz-Bravo; Fernando Arós; Miquel Fiol; et al. (Antioxidants, 2021)
Our aim was to assess whether long-term adherence to a Mediterranean diet (MedDiet) and leisure-time physical activity (LTPA) were associated with a lower initiation of cardiovascular drug use. We studied the association between cumulative average of MedDiet adherence and LTPA and the risk of cardiovascular drug initiation in older adults at high cardiovascular risk (PREvención con DIeta MEDiterránea trial participants) non-medicated at baseline: glucose-lowering drugs (n = 4437), antihypertensives (n = 2145), statins (n = 3977), fibrates (n = 6391), antiplatelets (n = 5760), vitamin K antagonists (n = 6877), antianginal drugs (n = 6837), and cardiac glycosides (n = 6954). One-point increases in MedDiet adherence were linearly associated with a decreased initiation of glucose-lowering (HR: 0.76 [0.71–0.80]), antihypertensive (HR: 0.79 [0.75–0.82]), statin (HR: 0.82 [0.78–0.85]), fibrate (HR: 0.78 [0.68–0.89]), antiplatelet (HR: 0.79 [0.75–0.83]), vitamin K antagonist (HR: 0.83 [0.74; 0.93]), antianginal (HR: 0.84 [0.74–0.96]), and cardiac glycoside therapy (HR: 0.69 [0.56–0.84]). LTPA was non-linearly related to a delayed initiation of glucose-lowering, antihypertensive, statin, fibrate, antiplatelet, antianginal, and cardiac glycoside therapy (minimum risk: 180–360 metabolic equivalents of task-min/day). Both combined were synergistically associated with a decreased onset of glucose-lowering drugs (p-interaction = 0.04), antihypertensive drugs (p-interaction < 0.001), vitamin K antagonists (p-interaction = 0.04), and cardiac glycosides (p-interaction = 0.01). Summarizing, sustained adherence to a MedDiet and LTPA were associated with lower risk of initiating cardiovascular-related medications.